PENINGKATAN EFISIENSI PENCELUPAN KAIN KAPAS BERBASIS PERLAKUAN KATIONISASI CHPTAC - Riswandi, Andri; Maulinawati, Susi; Kusumadewi, Afriani; Abdullah, Fadil (Politeknik META Industri Cikarang, 2025)
Reactive dyeing processes generally exhibit a relatively low fixation efficiency, ranging from 50% to 70%, which results in approximately 35% to 35% of the dye being discharged into the dyeing wastewater. In this study, cotton fabric was treated with a cationizing agent, CHPTAC, at a concentration of 5%, combined with different NaOH concentrations of 15%, 25%, and 35% relative to CHPTAC, using the exhaust method. The dyeing process was carried out using color Red Type A(vinyl sulfone type) and color Red Type B (monochlorotriazine type) reactive dyes. The results indicated that the cationized cotton fabric exhibited higher dye uptake compared to the untreated fabric. This improvement was confirmed by FTIR analysis, which showed the formation of N–H functional groups within the wavenumber range of 1580 cm⁻¹ to 3490 cm⁻¹. Furthermore, the color strength (K/S value) for vinyl sulfone dyed fabric increased from 1,65 for non-cationized samples to 3,31 for samples treated with 5% CHPTAC and 35% NaOH. Similarly, in monochlorotriazine dyeing, the K/S value increased from 2,04 for untreated fabric to 4,07 after the cationization process. The rubbing fastness test demonstrated satisfactory results, with dry rubbing values in the range of 4–5 and wet rubbing values between 3–4 and 4–5 for both vinyl sulfone and monochlorotriazine reactive dyes applied to 100% cotton fabric